Synthesis, electrochemical properties and catalytic behavior for electrochemical hydrogen production of [Ni(1, 3-bis(diphenylphosphino)propane)((2-mercaptopyridinate)-κN, S)]BF4. (15th February 2018) - Hamaguchi, Tomohiko; Kai, Keisuke; Konishi, Shohei; Ando, Isao
Graphical abstract: A new nickel complex, [Ni(1, 3-bis(diphenylphosphino)propane)((2-mercaptopyridinate)- κN, S )]BF4, was synthesized as a catalyst for electrochemical production of hydrogen from acid proton sources. The complex was synthesized under ambient condition and was air-stable. A catalytic cathodic current was observed using trifluoroacetic acid; however, it was not present using acetic acid. Abstract: A new nickel complex [Ni(1, 3-bis(diphenylphosphino)propane)((2-mercaptopyridinate)- κN, S )]BF4 was synthesized and characterized by NMR spectroscopy, an X-ray crystallographic study, elemental analysis and electrospray ionization mass spectroscopy. The complex was synthesized under ambient conditions and was air-stable. Catalytic behavior for electrochemical production of hydrogen was investigated by cyclic voltammetry. The cyclic voltammogram with acetic acid as a proton source was very similar to the voltammogram without the complex; however, significant catalytic cathodic current was observed when trifluoroacetic acid was used as the proton source. Differences between the behavior of the complex with different acids in cyclic voltammetry was also observed in UV–Vis spectrum. The possible catalytic mechanism for hydrogen production is discussed.